2021
DOI: 10.1186/s12888-021-03049-w
|View full text |Cite
|
Sign up to set email alerts
|

Combined pattern of childhood psycho-behavioral characteristics in patients with schizophrenia: a retrospective study in Japan

Abstract: Background Although epidemiological and genetic studies have provided scientific evidence that places schizophrenia into the framework of early neurodevelopmental disorders, the psycho-behavioral characteristics of children that later go on to develop schizophrenia have not been sufficiently clarified. This study aimed to retrospectively identify characteristics specific to patients with schizophrenia during childhood via their guardians’ reporting of these characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…First, we did not conduct medical interviews, including the structured interview for prodromal syndromes (SIPS) and the comprehensive assessment of ARMS (CAARMS), but used the TP scale, which has only seven items and was evaluated by the primary caregivers. Although previous studies showed an association between the TP scale and psychosis risk 14 , 15 , they may have underestimated or overestimated the children’s abnormal behaviors, and this observer bias was not considered in the present study. Second, regression analysis showed that hair zinc levels were significantly correlated with the TP scale ( T -score); nonetheless, the adjusted R 2 in the analysis was low, indicating that further validation is required regarding the use of hair zinc levels as a clinical biomarker.…”
Section: Strengths and Limitationsmentioning
confidence: 79%
See 2 more Smart Citations
“…First, we did not conduct medical interviews, including the structured interview for prodromal syndromes (SIPS) and the comprehensive assessment of ARMS (CAARMS), but used the TP scale, which has only seven items and was evaluated by the primary caregivers. Although previous studies showed an association between the TP scale and psychosis risk 14 , 15 , they may have underestimated or overestimated the children’s abnormal behaviors, and this observer bias was not considered in the present study. Second, regression analysis showed that hair zinc levels were significantly correlated with the TP scale ( T -score); nonetheless, the adjusted R 2 in the analysis was low, indicating that further validation is required regarding the use of hair zinc levels as a clinical biomarker.…”
Section: Strengths and Limitationsmentioning
confidence: 79%
“…The Child Behavior Checklist (CBCL) is a simple questionnaire tool developed by Achenbach that comprehensively evaluates children’s emotional and behavioral problems 51 . CBCL is widely used to predict mental disorders meeting Diagnostic and Statistical Manual of Mental Disorders criteria 52 54 , and the TP scale, a subscale of CBCL, has been shown to be an indicator of psychosis risk among adolescents 14 , 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…And specific CBCL subscales (Social, Attention and Thought Problems) were the strongest discriminator among those who screened positive for non-affective psychosis at age 21 (Scott et al, 2009;Welham et al, 2009). Hamasaki (Hamasaki, Nakayama, Hikida, & Murai, 2021) assessed adults with schizophrenia retrospectively and found elevated scores in similar subscales during childhood (Withdrawn, Thought Problems and Lack of Aggressive Behaviour).…”
Section: Introductionmentioning
confidence: 99%
“…Bleuler made many conceptual contributions, but perhaps, most relevant to this discussion is his view that psychotic symptoms were secondary to fundamental symptoms, including attentional problems. Research on the cognitive impairment of schizophrenia went forward, and its major features were reliably described: (i) all domains of cognition, including attention, executive function, secondary (storage) memory, working memory, and semantic memory may be affected; (ii) the pattern of deficits may vary widely among individuals with schizophrenia; (iii) the mean deficit in these domains may be 1–3 standard deviations below normal,[ 3 4 5 ] although about 15% of patients with schizophrenia test within the normal range in all domains;[ 6 ] (iv) for most patients, impairment is only slowly progressive after the first episode of psychosis;[ 7 8 ] and (v) some components of the deficit are present during childhood and early adolescence but usually in mild form. [ 7 9 ] This led to the conclusions that widespread decline in cognition occurs during the prodromal period (before the onset of psychosis), the first psychotic episode, or both and that prevention of the evolution of the cognitive deficit during these two periods might be of great value, if possible.…”
mentioning
confidence: 99%